Kajian Teologis Pelayanan Pastoral Terhadap Orang Miskin: Analisis Kesenjangan Teori Dan Praktik Di GBI SSS Jember - Feniwati; Manno, Daud; Heryanto, Doni (JURNAL LUXNOS, 2025)
Pastoral ministry to the poor is a biblical mandate that continues consistently from the Old Testament to the New Testament and remains relevant to the mission of the church today. However, in GBI SSS Jember there exists a significant gap between theological understanding and the practical implementation of pastoral ministry toward the poor. Conceptually, the church acknowledges God’s love and concern for the poor, yet practically this ministry has not been well-integrated theologically nor prioritized in church practice. This study aims to establish a solid theological foundation for pastoral ministry to the poor so that the church may serve holistically—addressing physical, spiritual, and social dimensions—based on love and humanitarian values. The research employs a qualitative method with a descriptive-analytic approach through structured and open interviews with church leaders and members of GBI SSS Jember to explore biblical-theological perspectives and their practical expressions in diaconal ministry. The findings reveal that the pastoral ministry to the poor in GBI SSS Jember remains sporadic and lacks integration between systematic theology and practical theology. As a result, the ministry has not yet addressed the root causes of poverty nor produced transformative impact within the congregation. The implication of this study is that the church must formulate a theologically grounded and contextually relevant model of pastoral ministry that embodies the prophetic and holistic example of Christ and the apostles, so that diaconal service moves beyond charity toward genuine spiritual and social transformation within the community of faith.